Chemical, physical and mineralogical properties associated with the hardening of some South African fly ashes - Campbell, Alex E (Department of Geological Sciences, 2016)
Coal combustion for power generation is relied on heavily in South Africa. The main residue from the combustion process is fly ash, with about 22 million tons being produced in 1994, of which only about 1 million tons is utilised, the remainder requiring disposal as waste. Various environmental impacts are associated with the disposal of fly ash in surface impoundments, including loss of usable land, contamination of groundwater, and production of wind-blown particulates, effects on vegetation and aesthetic impacts. Ultimately the disposal of fly ash in the mined-out underground workings is highly sought after, as it may limit many of the impacts which fly ash induces on the environment. The main purpose of this study was to assess the degree of hardening of four South African fly ashes from power stations at Kriel, Lethabo, Matla and Sasol in terms of their chemical, physical and mineralogical properties. Samples were taken of fresh and unweathered ashes from each power station. Unweathered ash samples analysed by XRFS were found to have high contents of Si0 2 (49.9-56.3%), Al 2 0 3 (27.2-31.5%), CaO (4.2-8.6%Y and Fez03 (3.1-3.9%) with varying contributions from loss on ignition (L.O.I.) (0.4-4.4%) and MgO (1.1- 2.2%). The major mineral phases detected in unweathered ash by XRD include quartz, mullite and glass, with smaller contributions from hematite and lime. Laser particle size analysis and liquid limit determination (Atterberg tests) were also conducted. The exceptionally high L.O.I of Sasol ash (4.4%) was attributed to the presence of partially burned coal, based on DTA and TGA investigation. Modulus of rupture experiments were conducted on briquettes (dimensions 7.0 x 3.5 x 1.0 em) of unweathered ash from Kriel, Matla, Lethabo and Sasol, which were wetted to their liquid limit and cured for 24 h under ambient conditions. The tests indicated that there is a strong linear relationship between total Ca content and the modulus of rupture for 3 of the 4 unweathered ashes. The fly ash from Kriel deviates from this relationship, providing evidence that other chemical (e.g. form of Ca) and physical factors (e.g. particle size) may also play a role in hardening.